Os odontoideum-induced sudden onset myelopathy following cervical extension injury in an adult—case report on challenges and management with 3D navigation technology - Sathish Muthu; Sathish Muthu; Guna Pratheep Kalanchiam; Hyun Jun Jang; Bong Ju Moon; Keun-su Kim (Frontiers in Surgery)
Os odontoideum is a relatively rare congenital anomaly of the upper cervical spine. It occurs due to developmental failure of the C2 odontoid process. Symptomatic patients develop instability resulting in cervical spinal cord compression. Surgical fixation is the management of choice in such patients to mitigate the risks of neurological worsening. On the other hand, such pathologies are challenging conditions to treat, mainly due to the surrounding delicate neurovascular structures and smaller bony anatomy of the atlas and axis. Especially in patients with variability in the normal anatomy of osseous and vascular structures, it is even more difficult to establish an effective stabilization strategy. Over the years, it has been proven that the use of pedicle screws is far superior to other techniques like sublaminar wiring in the cervical spine. However, it may not be possible in several cases due to anatomical constraints and lack of sufficient experience for early career surgeons to execute the surgical plan with ease and confidence. 3D-CT-based navigation has enabled real-time guidance for screw trajectory. They have significantly helped surgeons in the appropriate placement of surgical hardware, even with lesser surgical exposure and in minimally invasive techniques. We present the utilization of this technology in a case of sudden onset quadriparesis due to atlantoaxial instability secondary to Os odontoideum. This article highlights the effectiveness, safety, and precision of 3D-CT guidance in managing such complex case scenarios.